2012
DOI: 10.1007/s00702-012-0917-5
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal raphe neuronal activities are modulated by methylphenidate

Abstract: This study investigated the electrophysiological properties of the dorsal raphe nucleus (DR) neurons in response to the acute and repetitive administration of methylphenidate (MPH). Activities of DR neurons were recorded from non-anesthetized, freely behaving rats previously implanted bilaterally with permanent semi microelectrodes. The main findings were: (1) after initial (acute) administration of MPH (2.5 mg/kg i.p.) on experimental day one (ED1), 56 % of DR units significantly changed their firing rates. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…Previous experiments have shown that daily saline injections for three weeks do not alter behavioral locomotor activity, sensory evoked neuronal potentials, or electrophysiological neuronal firing rates (Yang et al, 2006a;b;c;d). Therefore, the activity after saline injection was used as control for the drug effect (Claussen and Dafny 2012; Frolov et al, 2015; Jones and Dafny, 2013; Salek et al, 2012; Tang and Dafny 2012; 2013; Yang et al, 2006b, 2007). To determine if MPD induced a significant change/response, multiple methods were employed as follow: the mean activity after treatment needs to be at least two standard errors (S.E.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments have shown that daily saline injections for three weeks do not alter behavioral locomotor activity, sensory evoked neuronal potentials, or electrophysiological neuronal firing rates (Yang et al, 2006a;b;c;d). Therefore, the activity after saline injection was used as control for the drug effect (Claussen and Dafny 2012; Frolov et al, 2015; Jones and Dafny, 2013; Salek et al, 2012; Tang and Dafny 2012; 2013; Yang et al, 2006b, 2007). To determine if MPD induced a significant change/response, multiple methods were employed as follow: the mean activity after treatment needs to be at least two standard errors (S.E.)…”
Section: Methodsmentioning
confidence: 99%
“…difference from the control firing rate. Because the firing rates did not hold up to normality assumptions used to determine parametric or non-parametric, significance was based also on the critical ratio test ( C.R.=1E-CE+C=±1.96=p<0.05) (C = control, E = drug activity) (Chong et al, 2012; Claussen and Dafny 2012; Dafny, 1975; 1982; Frolov et al, 2015; Jones and Dafny, 2013; Salek et al, 2012; Tang and Dafny 2012; 2013; Yang et al, 2006a;b;c). The following comparisons were made, from the three (0.6, 2.5, 10.0 mg/kg MPD) groups 1) neuronal activity recorded from all animals 2) neuronal activity recorded from animals expressing behavioral sensitization, and 3) neuronal activity recorded from animals expressing behavioral tolerance, to chronic MPD exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also reported that MPD induces an increase in DR neuronal activity directly and as measured by the expression of Fos-like immunoreactivity in DR neurons following treatment (Tang and Dafny 2013a; Tang and Dafny 2013b; Trinh et al, 2003). Adolescent mice have been shown to increase Fos expression in DR relative to other brain regions (Karanges et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…However, evidence from freely moving animals suggests that acute methylphenidate administration changes that activity of over half of the neurons in the DRN, in most cases increasing their firing rate [76]. Although the mechanism of action is unknown, again this means the drug is likely to produce an early increase in forebrain 5-HT levels without the need for a period of desensitisation.…”
Section: Serotonin Based Interventions For Adhd: Autoregulation Of Sementioning
confidence: 99%